MEMAKSIMALKAN PURCHASING MELALUI APLIKASI ACCURATE DI KANTOR PULSA 21 YELLOWCELL - Yunia Rachma Maulidah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This study provides an in-depth examination of YellowCell's Pulsa 21 Office's comprehensive utilization of the Accurate Application, with the primary objective of enhancing efficiency and precision in the realm of prepaid mobile credit purchases. This application plays a pivotal role in automating substantial portions of the purchasing process, offering real-time inventory monitoring, and significantly improving overall customer satisfaction. Employing a descriptive research approach, the study thoroughly delineates the application's characteristics, conditions, and associated phenomena. In a strategic endeavor, Pulsa 21 YellowCell has implemented a range of integrated solutions, including an intuitive user interface, seamless integration with delivery service providers, payment system optimization, and a continuous commitment to monitoring and enhancement. Additionally, they have overhauled logistics processes and harnessed automation technology to expedite order processing. Collectively, the widespread implementation of the Accurate Application has unequivocally bolstered Pulsa 21 YellowCell's proficiency and precision throughout the prepaid mobile credit purchase process, leading to elevated levels of customer satisfaction and ensuring their continued competitiveness within the telecommunications and prepaid mobile credit industry.